The Comparison of The United States Foreign Policy Against The Islamic World Under President Barack Obama and President Donald Trump Administration - Diana Mutiara Bahari; Ahmad Sahide (Universitas Muhammadiyah Yogyakarta, 2022)
The United States of America (USA) is an international concern, especially regarding the national election agenda. The presidential election of the world's leading superpower will impact the world's geopolitical order, such as the emergence of global political turmoil that has resulted in tensions in relations between the US and countries in the world, especially countries in the Islamic World. The 2016 US presidential election has captured international attention because it was won by a controversial figure, Donald Trump. The victory of Donald Trump to replace President Barack Obama marked a change in the style of US foreign policy towards the Islamic World. Therefore, the question arises of how the US foreign policy compares to the Islamic World in the era of President Obama and President Trump. This study uses a Foreign Policy Decision Making Theory. This study concludes that US foreign policy during the Obama administration was friendly to the Islamic World. On the other hand, US foreign policy during the Trump administration was not friendly to the Islamic World, which caused tension in relations between the US and the Islamic World.Keywords: US, Barack Obama, Donald Trump, Islamic World, Foreign Policy